Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1186/1742-4690-4-53
|View full text |Cite
|
Sign up to set email alerts
|

Primary T-cells from human CD4/CCR5-transgenic rats support all early steps of HIV-1 replication including integration, but display impaired viral gene expression

Abstract: Background: In vivo studies on HIV-1 pathogenesis and testing of antiviral strategies have been hampered by the lack of an immunocompetent small animal model that is highly susceptible to HIV-1 infection. Since native rodents are nonpermissive, we developed transgenic rats that selectively express the HIV-1 receptor complex, hCD4 and hCCR5, on relevant target cells. These animals display a transient low-level plasma viremia after HIV-1 YU-2 infection, demonstrating HIV-1 susceptibility in vivo. However, unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 54 publications
(115 reference statements)
3
59
1
Order By: Relevance
“…3A and B, flow cytometric quantification of cell surface-exposed mCD317 demonstrated potent (shRNA1, mean fluorescence intensity [MFI] of CD317 surface expression of 66) or intermediate (shRNA3, MFI of CD317 surface expression of 223; shRNA4, MFI of CD317 surface expression of 196) depletion of the restriction factor relative to that obtained with a control shRNA (MFI of CD317 surface expression of 832) in neomycin-selected S1A.TB cultures. To monitor the effect of variable mCD317 levels on S1A.TB cells on MLV replication, we performed infection studies with MLV-GFP, a replication-competent MoMLV which encodes an egfp gene driven from an IRES in the untranslated region between the env gene and the 3Ј LTR (14). Following infection with MLV-GFP at a low multiplicity of infection (MOI), moderate viral spread was detected in control shRNA-expressing (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3A and B, flow cytometric quantification of cell surface-exposed mCD317 demonstrated potent (shRNA1, mean fluorescence intensity [MFI] of CD317 surface expression of 66) or intermediate (shRNA3, MFI of CD317 surface expression of 223; shRNA4, MFI of CD317 surface expression of 196) depletion of the restriction factor relative to that obtained with a control shRNA (MFI of CD317 surface expression of 832) in neomycin-selected S1A.TB cultures. To monitor the effect of variable mCD317 levels on S1A.TB cells on MLV replication, we performed infection studies with MLV-GFP, a replication-competent MoMLV which encodes an egfp gene driven from an IRES in the untranslated region between the env gene and the 3Ј LTR (14). Following infection with MLV-GFP at a low multiplicity of infection (MOI), moderate viral spread was detected in control shRNA-expressing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…pMoMLV-GFP was constructed by introducing the egfp gene driven from an internal ribosomal entry site (IRES) into the untranslated region between the env gene and the 3Ј long terminal repeat (LTR) of MoMLV (GenBank accession no. AF033811.1) at unique NotI/ MluI sites, and viral stocks (MLV-GFP) were generated as previously reported (14). Both the virus titers and reverse transcriptase activities of MLV-GFP and the wild-type virus produced in BOSC cells were comparable (V. Hermann and H.-G. Kräusslich, unpublished data).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Specifically, the in vivo relationship of pharmacokinetics and the virological impact of raltegravir is still poorly defined, as dose-ranging studies of raltegravir showed equal efficacies of viral-load reduction across a range of doses (20,40,42). Animal models, such as HIV-susceptible transgenic Sprague-Dawley rats expressing the HIV-1 receptor complex (17,19,33,41), can support the preclinical validation process of antiviral compound candidates, allowing the quantification of their virological impacts and serum concentrations. In these in vivo models, an antiviral compound can be titrated from no effect to full effect, and mechanistic hypotheses can be probed under well-controlled experimental conditions.…”
mentioning
confidence: 99%